1980
DOI: 10.1093/nar/8.7.1613
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ionic strength on DNA-tigand unwinding angles for acridine and quinoline derivatives

Abstract: We have quantitatively examined the unwinding angles for the complexes of a related series of acridine and quinoline derivatives with DNA. Ethidium bromide was used as a control for determining superhelix densities at different ionic strengths. Relative to ethidium, 9-aminoacridine and quinacrine had an essentially constant unwinding angle of approximately 17 degrees at all ionic strengths tested. The apparent unwinding angle for chloroquine and 9-amino-1,2,3,4-tetrahydroacridine was found to be ionic strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 17 publications
6
44
0
1
Order By: Relevance
“…In one of the most important studies [9] it was shown that (i) the planar (aromatic) system of rings C and D ( Figure 1) is involved in an intercalative interaction with the duplex DNA whereas rings A and B protrude out of the helix interior into the minor groove where they interact with the minor-groove and/or top1 functionalities and (ii) all four protoberberines (1-4) depicted in Figure 3 unwind the B-DNA by approximately 11°due to the partial intercalative binding; this helix unwinding angle is in excellent agreement with the 10°value reported earlier by other inevestigators for the DNA binding of berberine, a structurally similar protoberberine to those studied here ( Figure 3) [23,24]. Recently, computer modeling techniques have also been employed to study the intercalative binding of some protoberberines with a d(ApT) 2 minihelix, but no correlation between the binding energy and the top1 poisoning activity was observed [9,10], indicating that the interaction of the drug with top1 residues makes a significant contribution to the stability of the ternary drug -DNA -top1 cleavable complex.…”
Section: Introductionsupporting
confidence: 89%
“…In one of the most important studies [9] it was shown that (i) the planar (aromatic) system of rings C and D ( Figure 1) is involved in an intercalative interaction with the duplex DNA whereas rings A and B protrude out of the helix interior into the minor groove where they interact with the minor-groove and/or top1 functionalities and (ii) all four protoberberines (1-4) depicted in Figure 3 unwind the B-DNA by approximately 11°due to the partial intercalative binding; this helix unwinding angle is in excellent agreement with the 10°value reported earlier by other inevestigators for the DNA binding of berberine, a structurally similar protoberberine to those studied here ( Figure 3) [23,24]. Recently, computer modeling techniques have also been employed to study the intercalative binding of some protoberberines with a d(ApT) 2 minihelix, but no correlation between the binding energy and the top1 poisoning activity was observed [9,10], indicating that the interaction of the drug with top1 residues makes a significant contribution to the stability of the ternary drug -DNA -top1 cleavable complex.…”
Section: Introductionsupporting
confidence: 89%
“…A maximum attainable value of 260 is provided by ethidium (27) and some related phenanthridines (40). Lower unwinding angles such as reported for acridines, (41,42), adriamycin, 120 (43) or daunorubicin, 100 (25) (25) also using sonicated calf thymus DNA and other similar experimental techniques analyzed the DNA viscosity enhancement of several planar aromatic molecules. They found that daunorubicin and 9-methoxyellipticine gave the expected increase in viscosity corresponding to the theoretical helix extension of 3.4 A per bound drug molecule.…”
Section: Discussionmentioning
confidence: 82%
“…We have shown that Acr(CH2)50H, the acridine derivative used to synthesize (Tp)n(CH2)5Acr, gives rise to the same spectroscopic behavior as quinacrine, even though the binding constants with DNA and synthetic polynucleotide duplexes are lower because of the lack of a positive charge on the substituent that is linked to the 9-amino group (our unpublished results). Quinacrine is known to intercalate between DNA base pairs and to unwind DNA by =17° (15).…”
Section: Resultsmentioning
confidence: 99%